Dinâmicas territoriais, dendeicultura e produção de culturas alimentares: o caso do município de Moju, PA - SANTOS, Cleison Bastos dos (Universidade Federal do Pará, 2023)
We have exposed in this work the doctorate thesis titled: LAND USE, OIL PALM FARMING AND PRODUCTION OF FOOD CROPS: An Analysis of Family Farmers Integrated with the Company Agropalma, in the municipality of Moju, PA, Brazil. We defend in the thesis that oil palm farming reduces food production in the locations where it is implemented. Our hypothesis is that this reduction occurs because the implementation of family agriculture projects with oil palm cultivation requires two essential resources: labor and land. In the specific case of pilot projects I (2002) and III (2005), integrated with the company Agropalma, the occupation of the area was different compared with the occupation of the area of project IV (2006). We aimed to analyze the impacts of oil palm farming expansion on food production by the family groups integrated with the productive chain of oil palm in the municipality of Moju. We wished, in this study, just as Nahum and Santos (2015), to geographically interpret the oil palm farming dynamics in the municipality of Moju starting at the category of used land (Santos; Silveira, 2001). We used, in this study, two methodologically complementary procedures: The analytical methodology based on the periodization and event concepts by Santos (2006) and Santos and Silveira (2001), which allowed us to think of a previous time (T1), the arrival of events (projects), and a period of time after the implementation of the projects (T2); and the operational methodology composed of literature review, cartographic surveys, structured and semi-structured interviews, and field work. The thesis is structured in three parts: In the first chapter, we analyze the land use by small family farmers prior to the arrival of family projects with oil palm crops. We used the peasant farm category by Woortmann (1983) to empirically show those dynamics. In those properties, land uses were subjected to different forms of work, solidarity bonds, and production systems. Their productions aimed at both consumption (use) and sale (exchange). In the second chapter, we show the events that shaped the family agriculture projects with oil palm farming in the Alto Moju and PA 150 regions, in the municipality of Moju. We analyzed, above all, the events that enabled the emergence of projects I (Arauaí I) and project II (Arauaí II), part of the Association of Community Development of the Arauaí Sector (Associação do Desenvolvimento Comunitário do Ramal do Arauaí - ASDECRA). In the third chapter, we analyze the transformations the process of integrating family projects to oil palm farming brought to land use, to the subjects, and to the production of food crops that fed the households and myriad remote homes.